Effects of temperature and salinity on the food consumption and growth of artificially-fed milkfish (Chanos chanos Forsskal) - Gauzon, Jose Enrique Diel (College of Fisheries, University of the Philippines in the Visayas, 1997)
Juvenile milkfish (mean weight 57.75+8.94 g) were fed an artificial diet (23% crude protein) at 6% of body weight feeding rate and reared at two temperature (240C + 10C and 340C + 10C)day did not exceed 2% of fish body weight in all treatments. Milkfish had higher feed consumption at high temperature (340C) but fish weight decreased. Further, temperature significantly influenced feed consumption, faecal egestion and apparent protein digestibility of milkfish in this experiment. The combination of low temperature (240C) and low salinity (24ppt) resulted to lowest feed conversion ratio (FCR), highest protein efficiency ratio (PER) and highest specific growth rate (SGR).